PENGARUH MODEL PEMBELAJARAN CCM CCA TERHADAP KEMAMPUAN PEMECAHAN MASALAH FLUIDA STATIS PESERTA DIDIK - Fitriana, Sirlaily; Makhrus, Muh.; Gunada, I Wayan; Ayub, Syahrial (Universitas Hamzanwadi, 2020)
This research is a Pre-experimental research with One Group Pretest-Posttest Design. This study aims to describe the students 'problem solving abilities during the learning process and determine the effect of CCM CCA learning models on problem solving skills and mastery of students' static fluid concepts. The study population was all students of class XI MIPA SMAN 4 Praya with a sampling technique using purposive sampling. The research sample was students in the three classes that were used as experimental classes that were given treatment in the form of learning using the CCM CCA learning model. Problem solving skills are obtained during the learning process by using LKPD which is equipped with problem solving ability instruments. The instrument used for problem-solving abilities uses test instruments in the form of test descriptions. Problem solving ability is measured by problem description. The conclusions obtained, namely 1) the level of problem-solving ability when the learning process is included in the medium category, 2) the CCM CCA learning model influences the ability of problem solving and mastery of students' static fluid concepts.